HDL proteome and apolipoproteins concentrations in severe ICU COVID-19 patients - Floran Begue; Bryan Veeren; Philippe Rondeau; Aline-Marie Florence; Simon Jamard; Philippe Montravers; Sébastien Tanaka; Olivier Meilhac; on behalf of French COVID Study Group (Lipids in Health and Disease)
Abstract Background SARS-CoV-2 infection affects both lipid metabolism and lung function. The severity of the disease has been associated with reduced levels of both high-density lipoprotein (HDL) and low-density lipoprotein cholesterol. Despite the crucial role that these nanoparticles play in SARS-CoV-2 infection, few studies have examined their structure during COVID-19 beyond HDL quantity. The study aimed to assess apolipoprotein levels in COVID-19 patients who either survived or died following ICU admission. In addition, ICU survivors and non-survivors were compared for HDL particle size and proteome. Methods Between February and April 2020, our study enrolled 37 COVID-19 patients upon their intensive care unit admission. Among them, 18 survived the disease, while 19 succumbed to it. We used mass spectrometry to assess plasma levels of 14 apolipoproteins and LCAT. Additionally, we analyzed HDL subpopulation distribution by utilizing native polyacrylamide gel electrophoresis. HDL particles were isolated from both surviving and non-surviving patients using ultracentrifugation, followed by characterization of their proteomes with NanoLC-MS/MS. Results Plasma apolipoproteins, including Apo A-II, Apo Cs (I, II, III), Apo H, Apo J, Apo M, and LCAT, were decreased in patients who did not survive COVID-19. However, no alterations were noted in the distribution of HDL subpopulations in relation to mortality. HDL composition was further altered based on mortality, displaying a decline in Apo H and paraoxonase 3. Conclusion In conclusion, we have shown an alteration in plasma apolipoproteins and HDL composition between surviving COVID-19 patients and non-survivors. Some markers, such as Apo H, are more predictive than baseline lipid concentrations such as HDL-C. These markers appear to provide a more accurate indication of mortality during COVID-19 compared with baseline lipid concentrations such as HDL-C.